Sanitary nursing pad containing polylactic acid fiber non-woven fabric surface layer and manufacturing method of sanitary nursing pad

By using 100% polylactic acid fiber nonwoven fabric as the surface material, combined with specific processes and structural design, the issues of skin-friendliness, biodegradability, and fluid conductivity of sanitary pad surface materials have been solved, achieving a soft, antibacterial, breathable, and environmentally friendly nursing effect.

CN121370504APending Publication Date: 2026-01-23JIANGSU XISILANTI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511514111.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing sanitary pads have poor skin-friendliness in their surface material, which can easily cause skin allergies or inflammation. They are also difficult to degrade and have poor absorbency, making them prone to backflow.

Method used

Made from 100% polylactic acid fiber nonwoven fabric surface material, it is produced through fiber opening, carding, web forming and consolidation processes, combined with hydroentangling, hot air or needle punching reinforcement processes to form a three-dimensional entangled structure, ensuring good mechanical properties and degradability. The surface material is designed with flow-guiding textures to improve flowability and breathability.

Benefits of technology

It achieves softness and skin-friendliness, good antibacterial properties, high biodegradability, excellent fluid conduction, and strong breathability, significantly reducing the risk of inflammation for users and environmental pollution, and improving user comfort and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121370504A_ABST
    Figure CN121370504A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of personal hygiene care products, and discloses a hygiene care pad containing a polylactic acid fiber non-woven fabric surface layer and a manufacturing method of the hygiene care pad. The surface layer is made of a 100% polylactic acid fiber non-woven fabric, is derived from a polylactic acid homopolymer or copolymer, is subjected to processes of opening, carding and the like, is consolidated by spunlace, hot air or needling, has the gram weight of 10-85 g / m, and has the characteristics of bacteriostasis and compostable degradation; the sanitary nursing pad is composed of the surface layer, the liquid absorption layer of the specific structure and the degradable bottom layer impermeable film, the problems that an existing nursing pad is poor in skin-friendly performance and flow guiding performance, pollutes the environment, is serious in back seepage and the like can be effectively solved, and the sanitary nursing pad has great application value in the field of personal sanitary nursing products.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of personal hygiene care products, in particular to a sanitary care pad with a non-woven fabric surface layer containing polylactic acid (PLA) fibers and a manufacturing method thereof, which is especially suitable for female menstrual care and the like. BACKGROUND

[0002] The surface layer of existing personal hygiene care products is mostly made of polyethylene (PE) punched film, chemical non-woven fabric and the like. These materials have poor skin friendliness, which can easily cause skin allergy or inflammation and the like. Moreover, such chemical materials are difficult to degrade, and will form a large amount of “white pollution” after being discarded. According to statistics, more than 5 million tons of garbage are generated annually due to the discarding of hygiene care pads, which brings heavy pressure to the ecological environment, and is contrary to the current concept of sustainable development. Therefore, it is urgent to seek environmentally friendly substitutes.

[0003] In order to improve the degradation performance of the hygiene care pad, some existing technologies attempt to use a mixture of polylactic acid fibers and other fibers to prepare the surface layer. For example, polylactic acid fibers are mixed with kapok fibers to prepare the surface layer, but the kapok fibers not only have high cost, but also have low strength, and the degradation rate of the mixed fibers is low; for another example, polylactic acid is mixed with cotton fibers, which improves the skin friendliness to a certain extent, but the cotton fibers are prone to mold, and the antibacterial property of the mixed system only depends on the weak acidity of a small amount of polylactic acid component, and the effect is limited.

[0004] In addition, the existing polylactic acid fiber and other fiber mixed surface layer also has deficiencies in the consolidation process. Conventional hot rolling consolidation is easy to cause the pores of the fibers to be blocked, thereby affecting the drainage property. In actual use, the re-imbibition amount is often greater than 0.6 g, and the user is easy to have a wet feeling; at the same time, the liquid absorption layer of the existing care pad has the problem of easy back seepage after absorbing liquid, the air permeability of the bottom anti-seepage film is poor, and long-term use is easy to feel stuffy and uncomfortable, which seriously affects the life quality of consumers. SUMMARY

[0005] The purpose of the present application is to provide a non-woven fabric surface layer material containing polylactic acid fibers, and a hygiene care pad using the surface layer material, to solve the problems of poor skin friendliness, easy to cause skin allergy or inflammation, easy to breed bacteria, easy to back seepage and non-degradable of the chemical fiber surface layer material of the hygiene care pad in the prior art.

[0006] The purpose of the present application can be achieved by the following technical solutions:

[0007] In a first aspect, the present application provides a non-woven fabric surface layer material containing polylactic acid fibers, wherein the non-woven fabric surface layer material is composed of 100% polylactic acid fibers, the polylactic acid fiber raw material is a polylactic acid homopolymer or a polylactic acid copolymer, the weight average molecular weight (Mw) of the polylactic acid is 30,000 to 300,000 g / mol, and a good balance between mechanical properties and degradability of the polylactic acid fibers can be ensured; the non-woven fabric surface layer material is prepared by a fiber opening, carding, webbing and consolidation process, and has a grammage of 10-85 g / m², a Staphylococcus aureus inhibition rate of ≥85%, and a compost degradation rate of ≥85%.

[0008] The preparation process of the non-woven fabric surface layer material is as follows:

[0009] S1: The polylactic acid fibers are subjected to opening treatment, such as two or three opening, and the beater speed is 500-900 r / min;

[0010] S2: Carding treatment, such as using a single-doffer carding machine with a main-doffer speed of 600-750 m / min or a roller carding machine with a main-doffer speed of 1000-1300 m / min;

[0011] S3: Webbing treatment, such as cross-laying or direct webbing;

[0012] S4: Finally, consolidation treatment is performed to prepare the non-woven fabric.

[0013] Further, the non-woven fabric is one of a spunlace non-woven fabric, a hot air non-woven fabric or a needle punch non-woven fabric; the spunlace consolidation process uses 2-4 spunlacing with a water pressure of 20-150 bar, and the fiber consolidation degree is ≥85%; the polylactic acid fibers are in a three-dimensional entanglement in the non-woven fabric, which can avoid pore blockage caused by hot rolling, and the three-dimensional entanglement of the fibers forms a continuous flow channel, which can improve the moisture conductivity; the hot air consolidation process uses a two-stage drying process, the temperature in the first zone is 75-95℃, the temperature in the second zone is 105-135℃, the drying time is 2-15 min, and the fiber consolidation degree is ≥85%; the hot air consolidation temperature is lower than the melting point of polylactic acid (155-170℃), which can effectively avoid fiber melting and ensure high porosity, thereby improving the air permeability; the needle punch consolidation process has a needle density of 80-120 needles / cm², and the fibers are tightly interwoven in the non-woven fabric, which can improve the structural stability of the non-woven fabric.

[0014] Further, the polylactic acid copolymer is one of a polylactic acid-glycolic acid copolymer, a polylactic acid-polyethylene glycol copolymer, a polylactic acid-polyvinyl alcohol copolymer or a polylactic acid-polycaprolactone copolymer.

[0015] Further, the polylactic acid fiber linear density is 1.0-9.0 dtex, and the length is 15-80 mm; the face layer material gram weight is further preferably 20-50 g / m², and the surface is provided with a flow guide pattern, which is a longitudinal flow guide pattern, a wave-shaped flow guide pattern, or a rhombic convex point pattern, wherein the convex point diameter is 1-5 mm, the interval is 1-5 mm, and the convex point height is 0.1-0.6 mm, which can further improve the flow guiding property or dry feeling.

[0016] Further, the non-woven fabric is treated with an organic silicon surfactant or an antistatic agent, the mass ratio of the treatment agent to water is 0.05 to 0.11:1, the spraying amount is 10-20%, the contact angle on the skin side is not higher than 60°, the contact angle on the liquid absorption layer side is not lower than 80°, and the moisture regain is 5-15%, which can realize one-way wet guiding and avoid fiber entanglement.

[0017] In a second aspect, the present application provides a sanitary care pad with a polylactic acid fiber non-woven fabric face layer, which comprises the face layer material, a liquid absorption layer, and a bottom impermeable membrane; the liquid absorption layer is any one layer or composite layer of cotton fiber, wood pulp fiber, polylactic acid short fiber, or super absorbent resin (SAP), and the super absorbent resin (SAP) is selected from one or any combination of cellulose grafting acrylic acid, polyacrylic acid sodium, or acrylamide copolymer, and further preferably, the super absorbent resin (SAP) is selected from cellulose grafting acrylic acid.

[0018] Further, the liquid absorption layer of the sanitary care pad is a gradient liquid absorption layer, wherein the weight fraction of the super absorbent resin (SAP) increases from top to bottom, and the gradient liquid absorption layer is divided into a first sublayer (SAP content 10-20 wt%), a second sublayer (SAP content 25-40 wt%), and a third sublayer (SAP content 45-60 wt%) from top to bottom, which can avoid local saturation and improve the liquid absorption ratio.

[0019] Further, the bottom impermeable membrane of the sanitary care pad is a polylactic acid / polyhydroxyalkanoate (PHA) composite membrane, a polylactic acid / polybutylene succinate (PBS) composite membrane, a polyhydroxyalkanoate (PHA) membrane, or other degradable polymer membranes, with a thickness of 20-50 μm, a moisture permeability ≥1200 g / (m²·24h), and a hydrostatic pressure resistance ≥3 kPa, which balances the impermeability and air permeability functions.

[0020] Still further, the sanitary care pad further comprises a side leakage prevention edge structure, which is made of the composite of the face layer material and the bottom impermeable membrane, and has a height of 3-8 mm, which can effectively prevent liquid side leakage.

[0021] Further, the health care pad further comprises a wing structure, the wing is made of the surface layer material and the bottom impermeable film, and the wing edge is provided with an arc-shaped cutting or a pressed edge with a width of 20-50 mm, so as to improve the fitting and comfort in use and prevent the edge from being raised.

[0022] Compared with the prior art, the present application has the following advantages:

[0023] (1) Skin-friendly and bacteriostatic: the 100% polylactic acid fiber non-woven fabric surface layer material is soft and skin-friendly, the fiber surface is weakly acidic (pH value 6.0-6.5), and the bacteriostatic rate of Staphylococcus aureus is ≥90%, which can effectively reduce the risk of inflammation and provide a healthier care for the user.

[0024] (2) Complete degradation: the surface layer, liquid absorption layer and bottom layer material are mainly made of degradable materials, and the overall composting degradation rate is ≥90%, which greatly reduces the pollution to the environment and has good environmental protection benefits.

[0025] (3) Excellent flow guiding property: whether it is the pore structure formed by the non-woven fabric or the surface texture design, the reperfusion amount of the care pad is ≤0.45g, and the collection time is ≤20s, which is significantly better than the commercially available products, and brings a dry experience to the user.

[0026] (4) Breathable and comfortable: the moisture permeability of the bottom impermeable film is ≥1200g / (m²·24h), which can effectively avoid the hot and humid feeling, and the reasonable design of the liquid absorption layer and the surface layer further improves the use comfort. BRIEF DESCRIPTION OF DRAWINGS

[0027] The present application will be further described below in conjunction with the drawings.

[0028] Figure 1 is a schematic view of a health care pad with a polylactic acid fiber non-woven fabric surface layer. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0030] It is apparent that the following description is merely an example or embodiment of the application and can be modified in other similar ways by those skilled in the art without creative effort, and therefore should not be interpreted as a deficiency of the disclosure.

[0031] In the description of the present application, the word "for example" is used to mean "serving as an example, instance, or illustration." Any embodiment described as "for example" is not necessarily to be construed as preferred or advantageous over other embodiments. The following description is presented to enable any person skilled in the art to make and use the application. In the following description, for purposes of explanation, specific details are set forth. It is apparent to those skilled in the art that the present application can be practiced without using these specific details. In other instances, well-known structures and processes are not elaborated in order not to obscure the description of the present application with unnecessary details. Thus, the present application is not intended to be limited by the embodiments shown, but is to be accorded with the widest scope consistent with the principles and features disclosed.

[0032] The experimental methods used in the specific embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used are conventional commercially available products unless otherwise specified and can be obtained through commercial channels.

[0033] In the present application, unless otherwise specified, "%" represents mass percentage.

[0034] Example 1

[0035] Preparation of the surface layer material: polylactic acid homopolymer fibers with a linear density of 3.5 dtex and a length of 51 mm and a weight average molecular weight (Mw) of 150000 g / mol were selected. After three passes of opening, the beater speeds were 520 r / min, 640 r / min, and 800 r / min, respectively. Then, the fibers were combed through a single-drum double-doffer carding machine at a main-drum speed of 650 m / min and a work roll speed of 45 m / min. Next, the fibers were cross-laid, and then three passes of hydroentanglement were performed at water pressures of 30 bar, 90 bar, and 110 bar, respectively. Subsequently, the fibers were immersed in a silicone surfactant with a concentration of 3% and a belt moisture rate of 80%. Finally, the fibers were dried at 120°C to produce a hydroentangled nonwoven fabric with a grammage of 30 g / m².

[0036] The health care pad is prepared by using the spunlace nonwoven fabric prepared in the above as the surface layer, and the liquid absorption layer is a three-layer gradient composite structure. The first sublayer is composed of cotton fiber and cellulose grafting acrylic acid superabsorbent resin (SAP) with a weight ratio of 85:15, and the gram weight is 40 g / m2. The second sublayer is composed of cotton fiber and cellulose grafting acrylic acid superabsorbent resin (SAP) with a weight ratio of 70:30, and the gram weight is 60 g / m2. The third sublayer is composed of cotton fiber and cellulose grafting acrylic acid superabsorbent resin (SAP) with a weight ratio of 50:50, and the gram weight is 90 g / m2. The bottom layer is a PLA / PHA blended film with a thickness of 35 μm and a moisture permeability of 1800 g / (m2·24h). The layers are bonded by 130℃ low-temperature hot melt glue, the side leakage edge is 3 mm, and the edge of the wing is arc-shaped cutting with a width of 40 mm.

[0037] Example 2

[0038] The poly-lactic acid surface layer material is woven by using the substantially same method as that in Example 1, and the health care pad is prepared by using the surface layer material, with the difference that the preparation process of the surface layer material is as follows: after cross-laying, two-stage oven hot air consolidation is performed, the temperature of the first zone is 85℃, and the temperature of the second zone is 120℃; then, 3% organic silicon surfactant with a pick-up rate of 80% is impregnated and dried at 120℃, thereby obtaining a hot air nonwoven fabric with a gram weight of 30 g / m2.

[0039] Example 3

[0040] The poly-lactic acid surface layer material is woven by using the substantially same method as that in Example 1, and the health care pad is prepared by using the surface layer material, with the difference that the preparation process of the surface layer material is as follows: after cross-laying, needle punching is performed, and the needle punching density is 100 needles / cm2; then, 3% organic silicon surfactant with a pick-up rate of 80% is impregnated and dried at 120℃, thereby obtaining a needle-punched nonwoven fabric with a gram weight of 30 g / m2.

[0041] Example 4

[0042] The poly-lactic acid surface layer material is woven by using the substantially same method as that in Example 1, and the health care pad is prepared by using the surface layer material, with the difference that the preparation process of the surface layer material is as follows: poly-lactic acid homopolymer fibers with a linear density of 4.0 dtex, a length of 56 mm, and a weight average molecular weight (Mw) of 200000 g / mol are selected. After three passes of opening, the beater speeds are 550 r / min, 660 r / min, and 850 r / min, respectively; then, the fibers are carded by a single-drum double-doffer carding machine at a main-drum speed of 650 m / min and a work roll speed of 45 m / min; then, cross-laying is performed, followed by three passes of water jetting at water pressures of 40 bar, 90 bar, and 115 bar, respectively; then, 4% organic silicon surfactant with a pick-up rate of 80% is impregnated, and finally, drying is performed at 120℃, thereby obtaining a spunlace nonwoven fabric with a gram weight of 35 g / m2.

[0043] Example 5

[0044] The polylactic acid surface layer material was woven by using the same method as in Example 1, and the sanitary nursing pad was prepared by using the surface layer material, with the difference that the preparation process of the surface layer material: polylactic acid fibers of polylactic acid-hydroxyacetic acid copolymer were selected, with a linear density of 4.0 dtex, a length of 56 mm, and a weight average molecular weight (Mw) of 200000 g / mol.

[0045] Example 6

[0046] The polylactic acid surface layer material was woven by using the same method as in Example 1, with the difference that the preparation process of the sanitary nursing pad: the liquid absorption layer was a three-layer gradient composite structure, the first sublayer was cotton fibers and sodium polyacrylate superabsorbent resin (SAP) with a weight ratio of 85:15, with a grammage of 50 g / m²; the second sublayer was cotton fibers and sodium polyacrylate superabsorbent resin (SAP) with a weight ratio of 70:30, with a grammage of 75 g / m²; the third sublayer was cotton fibers and sodium polyacrylate superabsorbent resin (SAP) with a weight ratio of 50:50, with a grammage of 100 g / m²; the bottom layer was a PLA / PHA blended film with a thickness of 35 μm and a moisture permeability of 1800 g / (m²·24h); each layer was bonded by 130°C low-temperature hot melt adhesive, with a side leakage prevention edge of 3 mm, and the wing edge was arc-shaped cutting with a width of 40 mm.

[0047] Comparative Example 1

[0048] The surface layer material was prepared by selecting polypropylene (PP) fibers with a linear density of 3.5 dtex, a length of 50 mm, and a weight average molecular weight (Mw) of 250000 g / mol, and a conventional hot rolling process was used to make a spunlace nonwoven fabric with a grammage of 40 g / m².

[0049] The sanitary nursing pad was prepared by using the above-prepared spunlace nonwoven fabric as the surface layer; the liquid absorption layer was fluff pulp and sodium polyacrylate superabsorbent resin (SAP) with a weight ratio of 70:30, with a grammage of 150 g / m²; the bottom layer was a polyethylene (PE) film with a thickness of 35 μm; each layer was bonded by 180°C high-temperature hot melt adhesive.

[0050] Comparative Example 2

[0051] The surface layer material was prepared by selecting polylactic acid and cotton blended fibers with a content of 50% each, with a linear density of 3.2 dtex, a length of 55 mm, and a weight average molecular weight (Mw) of 200000 g / mol, and a conventional hot rolling process was used to make a spunlace nonwoven fabric with a grammage of 32 g / m².

[0052] The sanitary nursing pad was prepared by using the same method as in Example 1, with the difference that the surface layer material.

[0053] Comparative Example 3

[0054] The surface layer material is prepared according to the same process as in Example 1.

[0055] The sanitary nursing pad is prepared as follows: the surface layer is the spunlace nonwoven fabric prepared above; the weight ratio of the fluff pulp to the sodium polyacrylate superabsorbent resin (SAP) in the liquid absorption layer is 70:30, and the grammage is 150 g / m2; the bottom layer is a polyethylene (PE) film with a thickness of 35 μm; and the layers are bonded by 180℃ high-temperature hot melt adhesive.

[0056] The surface layer materials and nursing pads prepared according to Examples 1-6 and Comparative Examples 1-3 are subjected to the following performance tests according to national or industrial standards, and the comprehensive performance test results are shown in Table 1.

[0057] Table 1. Comprehensive performance table of the nursing pads prepared according to Examples 1-6 and Comparative Examples 1-3

[0058]

[0059] As shown in Table 1, the sanitary nursing pad with the polylactic acid fiber nonwoven fabric surface layer provided by the present application has superior comprehensive performance, and also has better composting degradation rate, antibacterial performance, odor removal rate, moisture permeability and impermeability. Compared with Comparative Example 1 and Comparative Example 2, the antibacterial rates of the polylactic acid fiber nonwoven fabric surface layer prepared according to Examples 1-5 against Staphylococcus aureus and Escherichia coli are both more than 95%; and because the liquid absorption layer and the bottom layer impermeable film in Comparative Example 3 are made of common non-degradable materials, the composting degradation rate, odor removal rate, moisture permeability and impermeability are not as good as those of the examples of the present application.

[0060] The sanitary nursing pad with the polylactic acid fiber nonwoven fabric surface layer provided by the present application has superior comprehensive performance, and also has better composting degradation rate, antibacterial performance, odor removal rate, moisture permeability and impermeability. Compared with Comparative Example 1 and Comparative Example 2, the antibacterial rates of the polylactic acid fiber nonwoven fabric surface layer prepared according to Examples 1-5 against Staphylococcus aureus and Escherichia coli are both more than 95%; and because the liquid absorption layer and the bottom layer impermeable film in Comparative Example 3 are made of common non-degradable materials, the composting degradation rate, odor removal rate, moisture permeability and impermeability are not as good as those of the examples of the present application.

[0061] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A nonwoven fabric top sheet material containing polylactic acid fibers, characterized by, The non-woven fabric surface layer material is composed of 100% polylactic acid fibers, the polylactic acid fiber raw material is a polylactic acid homopolymer or a polylactic acid copolymer, the weight average molecular weight (Mw) of the polylactic acid is 30000-300000 g / mol; the non-woven fabric surface layer material is made by the fiber opening, carding, webbing and consolidation process, the grammage is 10-85 g / m², the antibacterial rate against Staphylococcus aureus is ≥90%, and the compost degradation rate is ≥90%.

2. The nonwoven top sheet material containing polylactic acid fibers according to claim 1, characterized in that, The non-woven fabric is one of spunlace non-woven fabric, hot air non-woven fabric or needle punch non-woven fabric; the spunlace reinforcement process adopts 2-4 spunlace, the water pressure is 20-150 bar, and the fiber consolidation degree is ≥85%; the hot air reinforcement process adopts two-stage drying, the temperature of the first zone is 75-95℃, the temperature of the second zone is 105-135℃, the drying time is 2-15 min, and the fiber consolidation degree is ≥85%; the needle punch reinforcement process adopts a needle punch density of 80-120 needles / cm².

3. The nonwoven top sheet material of claim 1, wherein the poly(lactic acid) fiber is a poly(L-lactic acid) fiber. The polylactic acid copolymer is one of polylactic acid-glycolic acid copolymer, polylactic acid-polyethylene glycol copolymer, polylactic acid-polyvinyl alcohol copolymer or polylactic acid-polycaprolactone copolymer.

4. The nonwoven top sheet material of claim 1, wherein the poly(lactic acid) fiber is a poly(L-lactic acid) fiber. The polylactic acid fiber linear density is 1.0-9.0 dtex, and the length is 15-80 mm; the grammage of the surface layer material is further preferably 20-50 g / m², and the surface is provided with flow guide lines, which are longitudinal flow guide lines, wavy flow guide lines or rhombic convex point lines.

5. The nonwoven top sheet material of claim 1, wherein the poly(lactic acid) fiber is a poly(L-lactic acid) fiber. The non-woven fabric is treated with an organosilicon surfactant or an antistatic agent, the mass ratio of the treatment agent to water is 0.05 to 0.11:1, the spraying amount is 10-20%, the contact angle of the skin-facing side is not higher than 60°, the contact angle of the liquid-absorbing layer-facing side is not lower than 80°, one-way wetting is achieved, and the moisture regain is 5-15%.

6. A sanitary care pad comprising a nonwoven poly lactic acid fiber face layer, characterized in that, From inside to outside, it comprises the surface layer material (1) of any one of claims 1-5, the liquid absorbing layer (2) and the bottom layer impermeable membrane (3); the liquid absorbing layer (2) is any one or composite layer of cotton fiber, wood pulp fiber, polylactic acid short fiber or super absorbent resin (SAP), the super absorbent resin (SAP) is selected from one or any combination of cellulose grafting acrylic acid, sodium polyacrylate or acrylamide copolymer, and further preferably, the super absorbent resin (SAP) is selected from cellulose grafting acrylic acid.

7. A hygiene pad according to claim 6, characterized in that The liquid absorbing layer (2) is a gradient liquid absorbing layer, wherein the weight parts of the super absorbent resin (SAP) increase from top to bottom, and the gradient liquid absorbing layer is divided into a first sublayer (2-1) with a SAP content of 10-20 wt%, a second sublayer (2-2) with a SAP content of 25-40 wt%, and a third sublayer (2-3) with a SAP content of 45-60 wt% from top to bottom.

8. A hygiene pad according to claim 6, characterized in that The bottom layer impermeable membrane (3) is a polylactic acid / polyhydroxyalkanoate (PHA) composite membrane, a polylactic acid / polybutylene succinate (PBS) composite membrane, a polyhydroxyalkanoate (PHA) membrane or other degradable polymer membrane, the thickness is 20-50 μm, the moisture permeability is ≥1200 g / (m²·24h), and the static water pressure resistance is ≥3 kPa.

9. A hygiene pad according to claim 6, characterized in that It also comprises a side leakage prevention edge structure (4) which is made of the surface layer material (1) according to any one of claims 1-5 and the bottom impermeable film (3), and has a height of 3-8 mm.

10. A hygiene pad according to claim 6, characterized in that It also comprises a wing structure (5) which is made of the surface layer material (1) according to any one of claims 1-5 and the bottom impermeable film (3), and has a width of 20-50 mm.